2018
DOI: 10.1136/postgradmedj-2017-135326
|View full text |Cite
|
Sign up to set email alerts
|

Performance of candidates disclosing dyslexia with other candidates in a UK medical licensing examination: cross-sectional study

Abstract: Performance was similar in AKT candidates disclosing dyslexia with other candidates once covariates associated with examination success were adjusted for. Candidates declaring dyslexia after initially failing the AKT were more likely to have a primary medical qualification outside the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 24 publications
4
29
1
Order By: Relevance
“…As in the previous study, we found that doctors from minority ethnic backgrounds and international medical graduates who had received their primary medical qualification outside the UK were more likely to declare dyslexia after initially failing the assessment. International medical graduates may be less likely to have been screened for dyslexia during their school or university education because of lack of testing and they and others may not disclose dyslexia because of stigma or perception of a negative impact on career progress .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…As in the previous study, we found that doctors from minority ethnic backgrounds and international medical graduates who had received their primary medical qualification outside the UK were more likely to declare dyslexia after initially failing the assessment. International medical graduates may be less likely to have been screened for dyslexia during their school or university education because of lack of testing and they and others may not disclose dyslexia because of stigma or perception of a negative impact on career progress .…”
Section: Discussionsupporting
confidence: 80%
“…Two previous studies investigating performance of medical students in undergraduate multiple‐choice tests and a further study investigating performance of doctors in an applied knowledge test for postgraduate medical licensing of general practitioners found no significant differences in the performances of candidates who declared dyslexia compared with those who did not . This latter study also showed differences in timing of declaration of dyslexia in international medical graduates (IMGs) (i.e.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Editor I read with great interest the article by Asghar et al, 1 exploring the impact of disclosing dyslexia, a specific learning difficulty (SpLD), on clinical examinations.…”
Section: On Disclosing Dyslexia and Other Specific Learning Difficultmentioning
confidence: 99%